Theoretical analysis of loss coefficients affecting pelton turbine performance - Jung, I.H.; Park, J.H.; Kim, Y.S.; Shin, Y.; Chung, J.T. (Korean Society of Mechanical Engineers, 2018)
To analyze the performance of Pelton turbines theoretically, the conventional loss models were examined and the theoretical formula suitable for the analysis was selected. A theoretical analysis method is presented and compared with the performance test results according to casing shape and volume to verify the theoretical analysis method. The performance test was performed for rectangular and circular casing, and the amount of windage loss in casing was analyzed quantitatively by casing design parameters through the proposed theoretical method. It is considered that the casing volume and shape have a dominant influence on the windage loss. As casing volume decreases, the windage loss decreases, and the efficiency increases inversely. The results of this study can be applied to the analysis and evaluation of losses occurring in Pelton turbines. Especially, the study will be useful for casing design that minimizes windage loss. ？ 2018 The Korean Society of Mechanical Engineers.
Keywords: Cascades (fluid mechanics); Analysis and evaluation; Efficiency increase; Friction loss; Pelton turbines; Pressure-retarded osmosis; Theoretical formula; Theoretical methods; Windage loss; Turbines